Binuclear Metal Chelates of 1,2,5,6-tetraphenyl-3,4-diaza-1,6-dihydroxyimino- 2,4-hexadiene with Pd(II) and Cu(II) - Sahu, K. (Asian Journal of Chemistry, 2010)
Binuclear metal chelates of 1,2,5,6-tetraphenyl-3,4 diaza-1,6 dihydroxyimino-2,4-hexadiene with Pd(II) and Cu(II) of the types Pd2L2·4H2O, Cu2LX4 (X = Cl or Br) have been prepared IR spectra suggest coordination of the ligand with the metal ions through azomethine nitrogen atoms in a bi-bidentate manner. The palladium complex is diamagnetic and is believed to be a dinuclear square planar complex. Its electronic spectra show the characteristic features of Pd(II) square planar complexes. Cu(II) complexes may have planar structures with two copper atoms bound in edge—on position to a single molecule of the ligand. Magnetic values show antiferromagnetic coupling between the metal centres.